Peningkatan Kompetensi Guru Teknologi Informasi di Lampung Selatan melalui Pelatihan Prompt Kecerdasan Buatan - Ridho Sholehurrohman; Igit Sabda Ilman; Agung Pambudi; Muhaqiqin; Muhammad Afdhaludin; Erin Eka Citra; Sandi Badiwibowo (Jurnal Pemberdayaan Masyarakat, 2025)
The rapid development of artificial intelligence (AI) technology has had a significant impact on the education sector, especially for Information and Communication Technology (ICT) teachers. Mastery of AI skills, particularly through prompt engineering techniques, is essential for teachers to create relevant, innovative, and curriculum-aligned questions and teaching materials. This community service activity aims to enhance the competencies of ICT teachers in Lampung Selatan, particularly at SMA Negeri 1 Kalianda and several other schools, in utilizing AI to support and enrich classroom learning. The main issue faced by the partner, the ICT teachers, is the lack of mastery of current technologies and limited knowledge of AI application in teaching. The implementation method includes literature study, face-to-face training, and evaluation of the activity's results. The training material focuses on introducing the basic concepts of AI, applying prompt engineering techniques, and using prompts to create AI-based questions that align with the school's learning needs. Evaluation results show that 89.4% of participants successfully mastered prompt engineering techniques and were able to implement them in creating questions and developing more effective teaching materials. This activity is expected to drive improvements in the quality of learning and support the sustainable implementation of AI in schools in Lampung Selatan.